Differences in the efficacy and safety among inhaled corticosteroids (ICS)/long-acting beta2-agonists (LABA) combinations in the treatment of chronic obstructive pulmonary disease (COPD): Role of ICS. (February 2015) - Latorre, M.; Novelli, F.; Vagaggini, B.; Braido, F.; Papi, A.; Sanduzzi, A.; Santus, P.; Scichilone, N.; Paggiaro, P.
Abstract: Inhaled corticosteroids (ICS) are frequently recommended for the treatment of asthma and COPD, often in combination with long-acting beta2-agonists (LABA), depending on the severity of the disease and/or on the specific phenotype. Several ICS/LABA combinations are currently available that differ in their pharmacokinetic characteristics and dose of both components. Thus, this review assesses differences in the efficacy and the safety profiles of the ICS components in the two more frequently used ICS/LABA combinations (budesonide/formoterol and fluticasone/salmeterol) for the management of COPD. Whereas the basic mechanism of action is similar for all ICS (binding with the intracellular glucocorticoid receptor, which mediates both genomic and non genomic effects), the pharmacokinetic and characteristics of ICS are quite different in terms of receptor affinity, bioavailability, lipophilicity and drug persistence in the airways. Fluticasone persists longer in airway mucus and requires more time to dissolve in the lining fluid and then enter the airway wall, whereas budesonide is cleared more quickly from the airways. Comparative efficacy of the two major ICS/LABA combinations recommended for the treatment of COPD show similar efficacy in terms of reduction of exacerbations, improvement in forced expiratory volume in the first second (FEV1) and quality of life. One retrospective cohort study suggested a greater efficacy for the budesonide/formoterol combination on hospital or emergency department admissions, oral corticosteroid courses, and addition of tiotropium, and an observational real-life study reported a greater reduction of COPD exacerbations with budesonide/formoterol than with fluticasom/salmeterol combination. Among the potential side effects of chronic ICS treatment in patients with COPD, recently the use of fluticasone or fluticasone/salmeterol combination has been associated with a higher prevalence of pneumonia in the major long-term studies. On the other hand, no similar increased risk of pneumonia has been reported in patients with COPD treated with the budesonide/formoterol combination. A recent population-based cohort study from the Quebec database showed that the adjusted odds ratio for having severe pneumonia was higher for fluticasone (2.1) than for budesonide (1.17) or other ICS (1.41). Of the ICS studied, only fluticasone demonstrated a dose-related increase in risk of pneumonia in patients with COPD. This difference between fluticasone and budesonide may be explained by the longer retention of fluticasone in the airways, with potentially greater inhibition of type-1 innate immunity. Therefore, the risk:benefit ratio should be evaluated thoroughly when choosing an ICS/LABA combination for patients with COPD.